Beset by the digital revolution successful retailers embrace technology that enhances customer value. Issue 6 (21st November 2016) - Blitz, Amy
Abstract : Purpose: The authorseeks to identify what strategies are successful companies using to navigate this ever-evolving retail landscape? And what strategies and best practices can be learned from the retail sector for thriving amid major economic transformations such as the current one? Design/methodology/approach: To help explain the divergence in performance across U.S. retailers given the same general macro context, the research focused on four companies – Target, Kohl's, JC Penney and Sears. Findings: Successful retailers focused on using technology to build value for customers first, and as a result shareholder value ensued. Practical implications: One key indicator of the connection between a company and its customers is the effectiveness of its social media presence. Originality/value: The article presents evidence that in order o leverage the full power of technology, retailers must make strategic investments in technology that enable them to understand who their customers are; determine what their customers most need and offer products and services that address these needs seamlessly in stores and online.